A community-integrated geographic information system study of air pollution exposure impacts in Colfax, LA. Issue 6 (3rd June 2022) - Richmond-Bryant, Jennifer; Odera, Matilda; Subra, Wilma; Vallee, Brenda; Tucker, Chloe; Oliver, Christopher; Wilson, Alyanna; Tran, Jessica; Kelley, Blair; Cramer, Jennifer Abraham; Irving, Jennifer; Guo, Chuqi; et al.
ABSTRACT: A community-integrated geographic information systems (CIGIS) study assimilating qualitative and quantitative information about human exposures and health was conducted in Colfax, Louisiana, which hosts a commercial open burn/open detonation thermal treatment (TT) facility that destroys hazardous waste from Superfund sites, explosives, military ordnances, and propellants. Fifty-eight percent of residents identified as Black, and median annual income was 16, 318, with 90% of the population living below the poverty line. We conducted oral history interviews of twenty-nine residents and mined public records to document the community's experiences. Interviews focused on themes of Colfax's history, changing community fabric, resident health, and air pollution. The oral histories and public comments by community members provided information about lived experiences, including several health conditions, toleration of noise and vibration, property damage, and resulting changes to activity levels. These statements provided insight into the extent of suffering experienced by the local community. We also ran dispersion models for dates in 2020 when the waste stream composition, mass, and burn/smoldering times were provided in the facility's public records. The dispersion models placed the air pollution at the homes of residents during some of the time, and waste stream records from the TT facility agree with community testimony about health effects based on the known health effects of those compounds. CIGIS integration of our community-based qualitative data and maps with quantitative air pollution dispersion model output illustrated alignment between community complaints of impacts to health and property, known toxicological information about waste stream compounds, and dispersion model output.